Information governance : concepts, strategies, and best practices - Smallwood, Robert F., 1959- (U.S.A : John Wiley & Sons, Inc., 2014)
"Proven and emerging strategies for addressing document and records management risk within the framework of information governance principles and best practicesInformation Governance (IG) is a rapidly emerging "super discipline" and is now being applied to electronic document and records management, email, social media, cloud computing, mobile computing, and, in fact, the management and output of information organization-wide. IG leverages information technologies to enforce policies, procedures and controls to manage information risk in compliance with legal and litigation demands, external regulatory requirements, and internal governance objectives. Information Governance for Business Documents and Records reveals how, and why, to utilize IG and leverage information technologies to control, monitor, and enforce information access and security policies. Written by one of the most recognized and published experts on document management Provides big picture guidance on the imperative for information governance and best practice guidance on electronic document and records management Crucial advice and insights for compliance and risk managers, operations managers, corporate counsel, corporate records managers, legal administrators, information technology managers, archivists, knowledge managers, and information governance professionals IG sets the policies that control and manage the use of organizational information, including social media, mobile computing, cloud computing, email, instant messaging, and the use of e-documents and records. This extends to e-discovery planning and preparation. Information Governance for Business Documents and Records provides step-by-step guidance for developing information governance strategies and practices to manage risk in the use of electronic business documents and records"--
Machine generated contents note: Foreword Preface Acknowledgments Part I: Information Governance Concepts, Definitions & Principles Chapter 1 The Onslaught of Big Data and the Information Governance Imperative Defining Information Governance IG is not a Project, But an Ongoing Program Why IG Is Good Business Failures in Information Governance Form IG Policies, Then Apply Technology for Enforcement Notes Chapter 2 Information Governance, IT Governance, Data Governance: What's the Difference? Data Governance IT Governance Information Governance Impact of a Successful IG Program Summing Up the Differences Notes Chapter 3 Information Governance Principles Accountability Is Key Generally Accepted Recordkeeping Principles(r) Contributed by Charmaine Brooks, CRM Assessment and Improvement Roadmap Who Should Determine IG Policies? Notes Part II: Information Governance Risk Assessment and Strategic Planning Chapter 4 Information Risk Planning and Management Step 1: Survey and Determine Legal and Regulatory Applicability and Requirements Step 2: Specify IG Requirements to Achieve Compliance Step 3: Create a Risk Profile Step 4: Perform Risk Analysis and Assessment Step 5: Develop an Information Risk Mitigation Plan Step 6: Develop Metrics and Measure Results Step 7: Execute Your Risk Mitigation Plan Step 8: Audit the Information Risk Mitigation Program Notes Chapter 5 Strategic Planning and Best Practices for Information Governance The Crucial Executive Sponsor Role Evolving Role of the Executive Sponsor Building Your IG Team Assigning IG Team Roles and Responsibilities Align Your IG Plan with Organizational Strategic Plans Survey and Evaluate External Factors Formulating the IG Strategic Plan Notes Chapter 6 Information Governance Policy Development A Brief Review of Generally Accepted Recordkeeping Principles(r) The IG Reference Model (IGRM) Best Practices Considerations Standards Considerations Benefits and Risks of Standards Key Standards Relevant to IG Efforts Making Your Best Practices and Standards Selections to Inform Your IG Framework Roles and Responsibilities Program Communications and Training Program Controls, Monitoring, Auditing and Enforcement Notes Part III: Information Governance Key Impact Areas Chapter 7 Information Governance and Legal Functions (Robert Smallwood with Randy Kahn, Esq., and Barry Murphy) Introduction to E-Discovery: The Revised 2006 Federal Rules of Civil Procedure (FRCP) Changed Everything Big Data Impact More Detail on the Revised FRCP Rules A Landmark E-discovery Case: Zubulake v. UBS Warburg Defensible Disposal: The Only Real Way to Manage Terabytes and Petabytes This section is by Randy Kahn, Esq. E-Discovery Techniques E-Discovery Reference Model The Intersection of IG and e-Discovery This section is by Barry Murphy Retention Policies and Schedules This section is by Robert Smallwood, edited by Paula Lederman, MLS Building on Legal Hold Programs to Launch Defensible Disposition This section is by Barry Murphy, edited by Robert Smallwood Destructive Retention of E-mail Newer Technologies That Can Assist in E-discovery Notes Chapter 8 Information Governance and Records and Information Management (RIM) Functions Records Management Business Rationale Why Is Records Management So Challenging? Benefits of Electronic Records Management Additional Intangible Benefits Inventorying E-Records The Generally Accepted Recordkeeping Principles(r) E-Records Inventory Challenges Records Inventory Purposes Records Inventorying Steps Appraising the Value of Records Ensuring Adoption and Compliance of RM Policy General Principles of a Retention Scheduling Developing a Records Retention Schedule Why Are Retention Schedules Needed? What Records Do You Have to Schedule? Inventory and Classification Rationale for Records Groupings Records Series Identification and Classification Retention of E-Mail Records How Long Should You Keep Old E-Mails? Destruction Retention of E-mail Event-Based Retention Scheduling for Disposition of E-Records Prerequisites for Event-Based Disposition Final Disposition and Closure Criteria Retaining Transitory Records Implementation of the Retention Schedule and Disposal of Records Ongoing Maintenance of the Retention Schedule Audit to Manage Compliance with the Retention Schedule Notes Chapter 9 Information Governance and Information Technology Functions Data Governance Steps to Governing Data Effectively Data Governance Framework Information Management IT Governance IG Best Practices for Database Security and Compliance Tying it All Together Notes Chapter 10 Information Governance and Privacy and Security Functions Cyber Attacks Proliferate The Insider Threat: Malicious or Not Privacy Laws Defense in Depth Controlling Access Using Identity Access Management Enforcing IG: Protect Files with Rules and Permissions Challenge of Securing E-Documents Apply Better Technology for Better Enforcement in the Extended Enterprise E-Mail Encryption Secure Communications Using Record-Free E-Mail Digital Signatures Document Encryption Data Loss Prevention (DLP) Technology The Missing Piece: Information Rights Management (IRM) Embedded Protection A Hybrid Approach: Combining DLP and IRM Technologies Securing Trade Secrets after Layoffs and Terminations Persistently Protecting Blueprints and CAD Documents Securing Internal Price Lists Approaches for Securing Data Once it Leaves the Organization Document Labeling Document Analytics Confidential Stream Messaging Notes Chapter 11 Business Considerations for a Successful IG Program (Barclay T. Blair, edited by Robert Smallwood) Changing Information Environment Calculating Information Costs Big Data Opportunities and Challenges Full Cost Accounting for Information Calculating the Cost of Owning Unstructured Information The Path to Information Value Challenging the Culture New Information Models Future State: What the IG-enabled Organization Will Look Like Moving Forward Notes Part IV: Information Governance for Delivery Platforms Chapter 12 Information Governance for E-Mail and Instant Messaging Employees Regularly Expose Organizations to E-Mail Risk E-Mail Polices Should Be Realistic and Technology-Agnostic E-Record Retention: Fundamentally a Legal Issue Preserve E-Mail Integrity and Admissibility with Automatic Archiving Instant Messaging Best Practices for Business IM Use Technology to Monitor IM Tips for Safer IM Notes Chapter 13 Information Governance for Social Media (Robert Smallwood and Dr. Patricia Franks) Types of Social Media in Web 2.0 Additional Social Media Categories Social Media in the Enterprise Key Ways Social Media Is Different from E-Mail and Instant Messaging Biggest Risks of Social Media Legal Risks of Social Media Posts Tools to Archive Social Media IG Considerations for Social Media Key Social Media Policy Guidelines Records Management Considerations for Social Media Emerging Best Practices for Managing Social Media Records Notes Chapter 14 Information Governance for Mobile Devices Current Trends in Mobile Computing Security Risks of Mobile Computing Securing Mobile Data Mobile Device Management (MDM) IG for Mobile Computing Building Security into Mobile Applications Best Practices to Secure Mobile Applications Developing Mobile Device Policies Notes Chapter 15 Information Governance for Cloud Computing Defining Cloud Computing Key Characteristics of Cloud Computing What Cloud Computing Really Means Cloud Deployment Models Greatest Security Threats to Cloud Computing IG Guidelines: Managing Documents and Records in the Cloud Managing E-Docs and Records in the Cloud: A Practical Approach Long-Term Content Migration Issues Cloud Services Lack Basic Records Management Capabilities Notes Chapter 16 SharePoint Governance for E-Records and Documents (Monica Crocker, CRM, PMP, edited by Robert Smallwood) Process Change, People Change Where to Begin the Planning Process Records Management Policy Considerations Roles and Responsibilities Establish Processes Training Plan Communications Plan Notes Part V: Long Term Program Issues Chapter 17 Long-Term Digital Preservation (Charles M. Dollar and Lori J. Ashley) Defining Long-Term Digital Preservation Key Factors in Long-Term Digital Preservation Threats to Preserving Records Digital Preservation Standards PREMIS Preservation Metadata Standard Recommended Open-Standard Technology-Neutral Formats Digital Preservation Requirements Long-Term Digital Preservation Capability Maturity Model(r) Scope of the Capability Maturity Model Digital Preservation Capability Performance Metrics Digital Preservation Strategies and Techniques Evolving Marketplace Looking Forward Notes Chapter 18 Maintaining an Information Governance Program and Culture of Compliance Monitoring and Accountability Continuous Process Improvement Why Continuous Improvement is Needed Notes Appendix A Information Organization and Classification: Taxonomies and Metadata (Barb Blackburn, CRM, with Robert Smallwood; edited by Seth Earley) Importance of Navigation and Classification When Is a New Taxonomy Needed? Taxonomies Improve Search Results Metadata and Taxonomy Metadata Governance, Standards, and Strategies Types of Metadata Core Metadata Issues International Metadata Standards and Guidance Records Grouping Rationale Business Classification Scheme, File Plans, and Taxonomy Classification and Taxonomy Prebuilt versus Custom Taxonomies Thesaurus Use in Taxonomies Taxonomy Types Business Process Analysis Taxonomy Testing: A Necessary Step Taxonomy Maintenance Social Tagging and Folksonomies Notes Appendix B Laws and Major Regulations Related to Records Management United States Canada* United Kingdom Australia Identifying Records Management Requirements in Other Legislation Notes Glossary About the Author About the Major Contributors Index .
Includes index.
Business Administration
Keywords: Information technology -- Management; Management information systems; Electronic records -- Management; BUSINESS & ECONOMICS / Information Management